Jīwana britānta dasa gurū sāhibāna mukkamala, arathāta, Dasa pātashāhīāṃ dā itihāsa, yā, Tawārīkha gurū khālasā - Amara Siṅgha (SAMP early 20th-century Indian books project, 1925)
Biographies of 10 gurus of the Sikhs.